Analyse technico-économique de projets d'élevage d'ombrine (Sciaenops ocellata) en cages flottantes à la Martinique - Houel, S; Falguiere, Jean-claude; Paquotte, Philippe (1996)
The availability in interesting sites and the zootechnical performances of tropical fish are two impo rt ant assets in favor of the development of fish farming in the Caribbean islands. This repor presents a technical and financial analysis of red drum farming projects in floating cages in Martinique(French West Indies). This project analysis makes it possible to compare the economic feasability of a small-scale production system with that of a semi-industrial one submitted to different technical constraints. The main criteria of the project analysis are the profitability of the funded capital, the financial feasability during the buildup period, the profitability at a steady state and the cost price. Production costs are hi gher in the the small-scale enterprises than in the semi-industrial ones, thanks to better capita] productivity and better labour productivity. An analysis of sensitivity to the variations ofbiological and economical parameters is also contained in the report. The results of these studies indicate that Caribbean fish farming could be profitable, due to the rapid buildup of the facilities and to the short production cycles. Nevertheless, attention should be paid to the risk of storms and hurricanes in this part of the world. Moreover, the analysis of sensitivity highlights the great influence of seed price. [NOT CONTROLLED OCR] Les bonnes performances zootechniques des poissons tropicaux et la disponibilité en sites propices sont deux atouts majeurs favorables au développement de l'aquaculture de poissons dans les îles des Caraïbes. Ce rapport présente l'adaptation d'un outil de simulation technico- économique à l'éleva ge de l'ombrine en cages flottantes dans le contexte martiniquais. Cet outil permet de disposer d'éléments de comparaison sur la faisabilité de deux systèmes de production, Fun de type artisanal et l'autre de type semi- industriel, soumis à des contraintes techniquesdifférentes : rentabilité du capital investi, faisabilité financière au démarrage, rentabilité en année de ...